Association between Non-Alcoholic Fatty Liver Disease and Carotid Intima-Media Thickness in Overweight and Obese Children - Homa-Sadat Vakilishahrbabaki (Journal of Research in Medical and Dental Science, 2018)
Non-Alcoholic Fatty Liver Disease (NAFLD) is the most prevalent diagnosed liver disease in developed societies, which is known as a disorder in liver function. In this regard, the measurement of the thickness of carotid intima-media layer is the most important marker for measuring atherosclerosis. The aim of this study was to investigate the relationship between non-alcoholic fatty liver and thickness of carotid artery in children and adolescents with overweight and obesity. This study was conducted as sectional and case control study in children between the ages 6-13 with overweight and obesity in Tehran, who were not suffering from other liver and kidney diseases. The presence or absence of fatty liver disease was diagnosed in patients under ultrasound imaging. After implementing ultrasonography, the samples were divided into two groups: fatty liver (n=126) and non-fatty liver (n=232). Using ultrasound test, the thickness of the carotid artery layer was measured. Cholesterol, triglyceride, LDL-C and HDL-C levels were measured in mg/dL based on blood tests. Systolic and diastolic blood pressure was also measured and recorded. The mean weight, the measure of waist circumference, body mass index, body fat percentage, FFM value, insulin levels and blood glucose levels in the patients group were significantly higher than those of healthy participants (P< 0.05). Also, the mean of high dense lipoprotein (HDL) was significantly lower in patients than in healthy participants. The presence of systolic blood pressure in patients with fatty liver was lower than healthy participants and diastolic blood pressure in patients with fatty liver was lower than in healthy participants. These differences were not statistically significant. There were also significant correlations between fatty liver and overweight. However, our results failed to confirm the association between fatty liver disease and carotid artery thickness increase in adolescents. There was a relationship between fatty liver disease and carotid artery thickness increase in adolescents, but other metabolic disorders may be effective in relation between fatty liver and atherosclerosis.